Evaluation of Social Reintegration Programs for Trauma Survivors in Communities Under Foreign Occupation in the Middle East - M. Agung Rahmadi; Luthfiah Mawar; Ayu Anastasyah; Aisyah Umaira; Nurma Handayani; Helsa Nasution; Nurzahara Sihombing; Naila Al Madina (Jurnal Ventilator, 2025)
This meta-review comprehensively examines the effectiveness of social reintegration programs designed for trauma survivors living in territories under foreign occupation in the Middle East, through a systematic analysis of 47 empirical studies with a total of 12,487 participants published between 2010 and 2024. The synthesis indicates that program success rates reached 73.8 percent with a 95 percent confidence interval (70.2–77.4), supported by a strong effect size in reducing PTSD symptoms with a Cohen's d value of 0.82. When effectiveness was compared across intervention approaches, community-based programs demonstrated a more substantial impact, with a correlation of r=0.67 (p<0.001), compared with individual interventions, which yielded a correlation of r=0.43 (p<0.01).